2018
DOI: 10.3390/ani8040059
|View full text |Cite
|
Sign up to set email alerts
|

Does Flooring Substrate Impact Kennel and Dog Cleanliness in Commercial Breeding Facilities?

Abstract: Simple SummaryIt is important to understand how the flooring substrate used in dog housing impacts dog health and well-being. Aspects to consider include paw, elbow, and hock health, the cleanliness of the dog, and the ability of the floors to be cleaned easily and thoroughly. This pilot study assessed the health and cleanliness of 118 dogs housed on three different types of flooring commonly found in commercial breeding kennels. No serious paw, elbow, or hock problems were identified. Thirty-one percent or fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 27 publications
3
6
0
Order By: Relevance
“…The quality of the floors of the facilities where the animals live for most of the time have a big effect on welfare, as do surfaces of paths where the animals move within the system, for example to milking, loading, unloading, crowding pen, or squeeze-chute. Ways in which characteristics such as material, nature of gaps in floors, drainage, roughness, slipperiness, and dirtiness can affect the welfare include: Physical damage to the animal's feet, discomfort, inadequate rest postures, or difficulty in moving; discomfort during rest due to hardness of the floor, excessive wet or dirt; and increased risk of lameness disorders, respiratory infections, mastitis or endometritis due to dirtiness [64][65][66][67]. The materials of the walls may damage the animals, walls should be free of irregularities and elements that could potentially cause injury such as wire, ties, nails, screws, metal projections, or wood clips [68].…”
Section: Housing Designmentioning
confidence: 99%
“…The quality of the floors of the facilities where the animals live for most of the time have a big effect on welfare, as do surfaces of paths where the animals move within the system, for example to milking, loading, unloading, crowding pen, or squeeze-chute. Ways in which characteristics such as material, nature of gaps in floors, drainage, roughness, slipperiness, and dirtiness can affect the welfare include: Physical damage to the animal's feet, discomfort, inadequate rest postures, or difficulty in moving; discomfort during rest due to hardness of the floor, excessive wet or dirt; and increased risk of lameness disorders, respiratory infections, mastitis or endometritis due to dirtiness [64][65][66][67]. The materials of the walls may damage the animals, walls should be free of irregularities and elements that could potentially cause injury such as wire, ties, nails, screws, metal projections, or wood clips [68].…”
Section: Housing Designmentioning
confidence: 99%
“…Previous research on the welfare of dogs presumably from CBKs conducted using data originating from dog owner reports [ 9 ] has lacked empirical evidence from direct observations. However, with advances in the development of dog welfare assessment tools and increased direct access to commercial dog breeding premises [ 10 , 11 , 12 , 13 ], researchers are beginning to better understand the behavior and health status of this population and how to assess their overall welfare in a more holistic way. It is important for researchers, breeding facility operators, and inspectors to have access to highly functional, validated, and easy to use tools designed to measure canine welfare in the field.…”
Section: Introductionmentioning
confidence: 99%
“…These include higher rates of fear and health problems in former breeding dogs, as well as lower rates of trainability when compared with pet dogs reportedly not sourced from breeding facilities [3,6,7]. However, recent pioneering work carried out by this research group at commercial dog breeding facilities in the Midwest (US), found very low prevalence of health issues and only moderate prevalence of fear responses toward an approaching unfamiliar person among breeding dogs [8][9][10]. The differences in the two bodies of work warrant discussion.…”
Section: Introductionmentioning
confidence: 95%
“…These papers referenced unidentified commercial breeding establishments, often using terms such as 'puppy farms' or 'mills'. The former term is typically used outside of the United States (US), and likely includes kennel types and management styles different from those used in United States Department of Agriculture (USDA)-licensed commercial kennels that were utilized in the on-site [6][7][8] studies. The problems with the latter term have already been noted.…”
Section: Introductionmentioning
confidence: 99%